Pelatihan dan Pendampingan Penyusunan Bahan Ajar IPAS Berbasis Kearifan Lokal Rote Ndao bagi Guru-Guru SD GMIT Oemaulain Kabupaten Rote Ndao - Treesly Y.N Adoe; Monica Bellandina Abolla (Prodi PGSD Unsultra, 2026)
This community service activity aims to improve teachers' pedagogical competence in developing local wisdom-based science teaching materials at GMIT Oemaulain Elementary School. The background to this activity is based on teachers' limited ability to connect science teaching materials to the cultural and environmental contexts of their students. The implementation method includes three main stages: needs analysis-based planning, a workshop on developing teaching materials, and intensive mentoring in developing teaching modules. The participants were all teachers at GMIT Oemaulain Elementary School. The results of the activity showed a significant increase in teachers' conceptual understanding and practical skills in designing contextual science teaching materials. Teachers were able to integrate local resources such as ikat weaving, palm trees, and coastal ecosystems into the teaching modules. Furthermore, the teachers' response to this activity was very positive, marked by high enthusiasm and active participation during the training and mentoring. Overall, this activity successfully strengthened teachers' pedagogical competence and encouraged more meaningful science learning for students. Integrating local wisdom has proven to be an effective strategy in increasing the relevance, creativity, and quality of learning in elementary schools.